Multimedia foundations : core concepts for digital design - Costello, Vic (Focal Press, 2012)
"Understand the core concepts and skills of multimedia production and digital storytelling using text, graphics, photographs, sound, motion, and video. Then, put it all together using the skills that you have developed for effective project planning, collaboration, visual communication, and graphic design. Presented in full color with hundreds of vibrant illustrations, "Multimedia Foundations" trains you in the principles and skill sets common to all forms of digital media production, enabling you to create successful, engaging content, no matter what tools you are using." -- Provided by publisher.